PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA KARYAWAN TERHADAP KOMITMEN ORGANISASI PADA PT. INDORACK MULTIKREASI TANGERANG (Studi kasus pada Divisi Warehouse) - Trisavinaningdiah, Amelia (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2021)
The purpose of this study was to determine the effect intended overall and partial between culture organizations, employee job satisfaction and commitment to the PT. Indorack Multikreasi. Methods used in this research is by distributing questionnaires to employees is using a Likert scale, respondents who used as many as 65 employees, using SPSS 20 software programs, data analysis performed using validity, reliability and correlation of multiple linear regression. Sampling techniques were obtained from a sample of 65 respondents, data analysis techniques using multiple linear regression. The results showed that; (1) Cultural organizations significant effect on organizations commitment; (2) Job satisfaction significantly influence organizatins commitment; (3) Organization culture and job satisfaction significantly influence organizations commitment